Specific covalent inhibition of MALT1 paracaspase suppresses B cell lymphoma growth - Fontán, Lorena (J Clin Invest, 2018)
The paracaspase MALT1 plays an essential role in activated B cell–like diffuse large B cell lymphoma (ABC DLBCL) downstream of B cell and TLR pathway genes mutated in these tumors. Although MALT1 is considered a compelling therapeutic target, the development of tractable and specific MALT1 protease inhibitors has thus far been elusive. Here, we developed a target engagement assay that provides a quantitative readout for specific MALT1-inhibitory effects in living cells. This enabled a structure-guided medicinal chemistry effort culminating in the discovery of pharmacologically tractable, irreversible substrate-mimetic compounds that bind the MALT1 active site. We confirmed that MALT1 targeting with compound 3 is effective at suppressing ABC DLBCL cells in vitro and in vivo. We show that a reduction in serum IL-10 levels exquisitely correlates with the drug pharmacokinetics and degree of MALT1 inhibition in vitro and in vivo and could constitute a useful pharmacodynamic biomarker to evaluate these compounds in clinical trials. Compound 3 revealed insights into the biology of MALT1 in ABC DLBCL, such as the role of MALT1 in driving JAK/STAT signaling and suppressing the type I IFN response and MHC class II expression, suggesting that MALT1 inhibition could prime lymphomas for immune recognition by cytotoxic immune cells.